2020
DOI: 10.1186/s12913-020-05141-5
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on program mis-implementation among U.S. local public health departments

Abstract: Background: Public health resources are limited and best used for effective programs. This study explores associations of mis-implementation in public health (ending effective programs or continuing ineffective programs) with organizational supports for evidence-based decision making among U.S. local health departments. Methods: The national U.S. sample for this cross-sectional study was stratified by local health department jurisdiction population size. One person was invited from each randomly selected local… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 51 publications
(96 reference statements)
2
8
3
Order By: Relevance
“…These factors demonstrated an inverse relationship with mis-implementation outcomes (e.g., as agency capacity increased, the association with mis-implementation rates decreased). These ndings are consistent with our earlier study among US local health departments, which found organizational supports for EBDM were associated with lower perceived frequency of inappropriate continuation [21]. This suggests agency culture and capacity are signi cant protective factors against mis-implementation in multiple public health organizations rather than the skills of individual staff.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These factors demonstrated an inverse relationship with mis-implementation outcomes (e.g., as agency capacity increased, the association with mis-implementation rates decreased). These ndings are consistent with our earlier study among US local health departments, which found organizational supports for EBDM were associated with lower perceived frequency of inappropriate continuation [21]. This suggests agency culture and capacity are signi cant protective factors against mis-implementation in multiple public health organizations rather than the skills of individual staff.…”
Section: Discussionsupporting
confidence: 91%
“…Compared with previous pilot work, perceived frequency of mis-implementation in SHD was higher in this study (36.5% vs 50.7% for inappropriate termination and 24.7% vs 48.5% for inappropriate continuation), although some of this difference may be attributable in part to updates to the mis-implementation survey item de nitions and changes in the approach to categorization of responses [9,10,21]. In earlier studies, the recoded dichotomized mis-implementation variables only included the often/always response.…”
Section: Limitationscontrasting
confidence: 90%
“…Compared to previous pilot work, perceived frequency of mis-implementation in SHD was higher in this study (36.5% vs 50.7% for inappropriate termination and 24.7% vs 48.5% for inappropriate continuation), although some of this difference may be attributable in part to updates to the mis-implementation survey item de nitions and changes in the approach to categorization of responses (9,10,21). In earlier studies, the recoded dichotomized mis-implementation variables only included the often/always response.…”
Section: Limitationscontrasting
confidence: 90%
“…These concepts support the factors that inform our original mis-implementation framework (8). In a cross-sectional U.S. study of local health departments, higher perceived organizational supports for EBDM were associated with lower perceived frequency of inappropriate continuation (21). In cross-country comparisons of mis-implementation involving Australia, Brazil, China, and the United States, leadership support and political contexts were common factors in whether chronic disease programs continued or ended inappropriately across four countries (22).…”
Section: Introductionmentioning
confidence: 52%
“…Preventing program mis-implementation is, therefore, necessary to sustain public health efforts and resources needed to improve health and well-being. In this context, mis-implementation refers to the inappropriate continuation of ineffective programs (17). Because executive management is responsible for making decisions such as approving or disapproving the continuance of a program, it is important to understand the attributes of public health leaders in preventing program mis-implementation.…”
Section: Introductionmentioning
confidence: 99%